Factors Affecting Student's Interest in Determining Majors Higher Education in Era 4.0 - Dela, Rilma Maya; Wijaya, Tony (Dinamika Pendidikan, 2022)
This study aimed to determine the factors that affect student interest in choosing majors in higher education in the 4.0 era. In the 4.0 era, secondary schools need to prepare students to make wise decisions in terms of choosing a college major that suits their future career goals. This research was a quantitative method with data collection techniques through observation and questionnaires to 263 class XII students of SMAN 1 Sambas. Data on graduates who worked not according to the study program showed an increase from 2017 to 2021, namely 60% to 80%. From the results of factor analysis, 7 variables formed 2 factors, namely internal environmental factors with a coefficient value of 61.06% consisting of parents, peers, personality, self-potential, and external environmental factors with a coefficient value of 12.51% consisting of opportunities for work, social environment, and future expectations. Internal environmental factors with a coefficient of 61.06% were the dominant factors that affected student interest in choosing college majors. Thus, the seven variables affected student interest in choosing majors in higher education in the 4.0 era.